Literature Review How Social Media Affects Student’s Learning and Education: Bibliometric Analysis - Prawidyaningrum, Sekar Ayu; Suprapto, Nadi (Universitas Negeri Surabaya, 2024)
This research uses bibliometric analysis to fill in the gaps and present an overview of how social media influences students' learning and education from 2014 to 2024. The precise goals of this study are to examine the kind of publication, contributing nation, top authors cited, and top source title, map research patterns, and determine which social media platform was utilized the most for the research. The metadata is from the Scopus database, while the mapping is from the VOSviewer database, which contains 108 research. The results suggest that the publishing of the influence of social media on students' learning and education has risen over time, with the most common kind of publication being an article, and the United States is the most prolific. Y.R. Chassiakos is the most referenced author, with Computers and Education being the most popular source titles. Mapping of research trends are: 1) social medium effect for motivation, behavior, and attitude; 2) Type of learning models such as e-learning, and blended learning; 3) assessment for education; 4) Social media platform; 5) access to internet; 6) Online learning performances; 7) Teaching strategy because pandemic. The top 3 social media platforms from media that the studies used were YouTube, Twitter, and Facebook.